Biology of extracellular vesicles and the potential of tumor-derived vesicles for subverting immunotherapy of cancer - Theresa L Whiteside (Journal for ImmunoTherapy of Cancer)
Extracellular vesicles (EVs) are produced by all living cells and are present in all body fluids. EVs are heterogeneous in size, biogenesis, molecular/genetic content and functions. They constitute a part of the intercellular communication system. Among them, a subset of small EVs (sEVs) (30–150 nm) originating in the tumor cell endosomes and often referred to as “tumor cell-derived exosomes” have been of special interest. Tumors have adapted sEV they produce to promoting their own survival. Plasma of patients with cancer contains variably elevated numbers of tumor-derived sEV called “TEX,” which differ from circulating sEV produced by non-malignant cells by the immunosuppressive phenotype and the molecular/genetic content. Immunosuppressive molecular profiles and abilities to signal, enter and functionally reprogram a variety of recipient cells enable TEX to exert pro-tumor effects that promote tumor resistance to immunotherapy. This review describes phenotypic and functional attributes of TEX that underline their reprogramming capabilities. It also considers mechanisms responsible for TEX pro-tumor activities and the potential significance of TEX signaling for responses of patients with cancer to immune therapies.